Toxic high streets. Issue 2 (4th March 2017) - Townshend, Tim G.
Abstract : People in deprived neighbourhoods live shorter and unhealthier lives than those in less deprived ones. Socio-economic status alone does not explain the difference and there is increasing evidence that the physical environments in which people spend their lives are implicated in health disparities. Traditional shopping streets in the UK have changed out of all recognition in the last few decades. This paper explores the evidence around exposure to unhealthy shops and services and how this may impact on communities. The work underlines the need to consider these potentially unhealthy areas more holistically. The research concludes that while restrictive planning policies to prevent proliferation of some of these uses may have some currency, more proactively urban designers need to fundamentally rethink these places and what they offer to the people they serve.